Delivery of radiation therapy of large target volumes in Hodgkin's disease using IMRT technique: A dosimetric case study. Issue 2 (May 2016) - Chan, E.H.; Ryan, M.J.
Abstract: Radiation therapy techniques for early stage Hodgkin's disease (HD) include simple parallel-opposed-pair (POP) and Intensity-Modulated Radiation Therapy (IMRT). This case report compared the dosimetry achieved with POP and IMRT by evaluating target volumes and organs at risk (OAR). It showed that the IMRT technique could be a valuable technique when treating HD. Optimal target coverage can be achieved while at the same time reducing dose given to critical structures such as lung and thyroid. Highlights: Comparing POP and IMRT technique for Hodgkin's disease with large target volumes. Our dosimetric data of IMRT showed better target coverage. IMRT also showed the most significant reduction in lung and thyroid doses.